Aromatic sulphonamides of aziridine-2-carboxylic acid derivatives as novel PDIA1 and PDIA3 inhibitors - D. Zelencova-Gopejenko; V. Andrianov; I. Domracheva; I. Kanepe-Lapsa; M. Milczarek; M. Stojak; K. Przyborowski; F. A. Fedak; M. Walczak; K. Kramkowski; J. Wietrzyk; S. Chlopicki; et al. (Journal of Enzyme Inhibition and Medicinal Chemistry, 2023)
In this study, we report a series of newly synthesised sulphonamides of aziridine-2-carboxylic acid (Az-COOH) ester and amide analogues as potent protein disulphide isomerase (PDI, EC 5.3.4.1) inhibitors. The inhibitory activity on PDI was determined against recombinant human PDIA1 and PDIA3 proteins using an insulin reduction assay. These compounds in low micromolar to low nanomolar concentrations showed the effective in vitro inhibitory properties of PDIA1 with weaker effects on PDIA3. Complexes of 15N- and 15N,13C- uniformly labelled recombinant human PDIA1a with two PDIA1 inhibitors were produced and investigated by a protein nuclear magnetic resonance (NMR) spectroscopy. It was found that both C53 and C56 of the PDIA1 enzyme were involved in covalent binding. Finally, in a range of pharmacological studies, we demonstrated that investigated compounds displayed anti-cancer and anti-thrombotic activity. These findings demonstrate that sulphonamides of Az-COOH derivatives are promising candidates for the development of novel anti-cancer and anti-thrombotic agents.